Community based monitoring and public service delivery: Impact, and the role of information, deliberation, and jurisdictional tier - Kabunga, Nassul; Miehe, Caroline; Mogues, Tewodaj; Van Campenhout, Bjorn (International Food Policy Research Institute, 2020)
To improve public service delivery, the Government of Uganda organizes community forums-popularly known as barazas-where citizens receive information from government offcials, and get the opportunity to directly engage with them. We run a cluster randomized control trial to assess the impact of this policy intervention on public service delivery in agriculture, health, education, and infrastructure. Using a factorial design, we further test the relative importance of the two main components of the intervention-information provision and citizen engagement. we also compare the effectiveness of barazas organized at the district level to the effectiveness of barazas organized at the sub-county level. Using a strictly pre-registered confirmatory analysis, we find no impact of the intervention on general public service delivery, but there are some indications that sub-county level barazas increase outcomes in the agricultural sector. A more exploratory part that looks at individual outcomes, potential mechanisms, and heterogeneous treatment effects suggests localized impacts of barazas in the areas of agricultural extension services and agricultural input distribution, access to drinking water, and school enrollment and infrastructure.